Flexland in wording.: De reactie en strategie van de vakbeweging ten aanzien van flexibilisering in Nederland in de jaren tachtig. - Kösters, Rosa; Van Diepen, Loran; Van Dijk, Moira; Van Rossum, Matthias (TSEG - The Low Countries Journal of Social and Economic History, 2021)
Internationally, the 1980s marked a shift in economic policy. In the Netherlands, it was the decade of the supposedly moderate neoliberal turn and of the first round of flexibilization. Nowadays, the degree of flexibility of the Dutch labour market is exceptionally high compared to neighbouring countries. This article examines how the trade union movement in the 1980s responded to increasing flexibilization, which strategy was used, and how this contributed to early Dutch flexibilization. In contrast to the literature with an institutional perspective, this article analyzes the trade union movement from a social-historical perspective and as a social movement organization. As a result, it argues that the effects of rising flexibilization were signalled very early on within the trade unions. Be that as it may, both the priorities that followed from the agreements with employer organizations and the internal dynamics, were decisive for the trade union movement’s relatively late and unassertive responses towards the flexibilization of labour in the 1980s.